2012
DOI: 10.1371/journal.pone.0052907
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plant Tissue and Vaccine Formulation on the Oral Immunogenicity of a Model Plant-Made Antigen in Sheep

Abstract: Antigen-specific antibody responses against a model antigen (the B subunit of the heat labile toxin of enterotoxigenic Escherichia coli, LTB) were studied in sheep following oral immunisation with plant-made and delivered vaccines. Delivery from a root-based vehicle resulted in antigen-specific immune responses in mucosal secretions of the abomasum and small intestine and mesenteric lymph nodes. Immune responses from the corresponding leaf-based vaccine were more robust and included stimulation of antigen-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, some important issue to consider are how the differences in the ruminant gut might affect the vaccine and whether the plant-bioencapsulated antigen would still be viable once the plant material reaches the intestine. Although there are numerous studies reporting immunogenicity of orally delivered plant-made vaccines in humans and small animal models, only a few have successfully demonstrated their efficacy in ruminants [7074]. The concept of transgenic plant-based vaccines has been successfully employed by Pelosi et al in their study on antigen-specific antibody responses against a model antigen (the B subunit of the heat labile toxin of enterotoxigenic E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some important issue to consider are how the differences in the ruminant gut might affect the vaccine and whether the plant-bioencapsulated antigen would still be viable once the plant material reaches the intestine. Although there are numerous studies reporting immunogenicity of orally delivered plant-made vaccines in humans and small animal models, only a few have successfully demonstrated their efficacy in ruminants [7074]. The concept of transgenic plant-based vaccines has been successfully employed by Pelosi et al in their study on antigen-specific antibody responses against a model antigen (the B subunit of the heat labile toxin of enterotoxigenic E .…”
Section: Discussionmentioning
confidence: 99%
“…The delivery resulted in antigen-specific immune responses in mucosal secretions of the abomasum, small intestine and mesenteric lymph nodes. These findings suggest that the orally administered plant-bioencapsulated antigens are still viable after the passage through the rumen and elicit mucosal and systemic immune responses in sheep [70]. …”
Section: Discussionmentioning
confidence: 99%
“…While tomato yielded the least amount of antigen overall, the antigen accumulation was reasonable when compared to other plant systems producing LTB [5759]. Unfortunately, oral delivery of vaccine antigens within hairy root tissue has proven less efficient than other plant tissues perhaps due to the cell walls being too thick and not releasing enough antigen from the cells at optimal locations throughout the digestive tract [60,61]. Secretion or purification of recombinant proteins from hairy roots may prove to be the more realistic approach for this platform.…”
Section: Available Molecular Tools For Protein Production In Solanmentioning
confidence: 99%
“…Such a scenario may explain why low antibody levels were reported in pre-challenge period in our study. Further, also other studies have demonstrated plant-made vaccine efficacy in ruminating animals and have reported specific mucosal and systemic responses ( 44 47 ). Thus, oral delivery of plant-made vaccines is a viable alternative in ruminant vaccination.…”
Section: Discussionmentioning
confidence: 93%